PENGARUH KEPEMIMPINAN, MOTIVASI DAN KEMAMPUAN INTELEKTUAL TERHADAP KINERJA PEGAWAI PADA KANTOR WILAYAH BADAN PERTANAHAN NASIONAL PROVINSI SUMATERA SELATAN - Sulbahri Madjir (JURNAL KOMPETITIF, 2014)
ABSTRACTThis study about the effect of leadership, motivation and intellectual ability to employee performance areas offices of National Land Agency of South Sumatra Province. The analysis showed leadership (X1), motivation (X2) and the ability of intelligentsia (X3) jointly affect employee performance (Y) of 97.4%, while the remaining 2.6% is explained by other factors not examined. Results obtained from the regression equation y = 4.722 + 0.905 + 0.595 X1 + 0.546 X2 + X3 e. From the results of hypothesis testing, to test F can be concluded that there is a significant effect of leadership (X1), motivation (X2) and intellectual ability (X3) jointly to employee performance (Y) Office of the National Land Agency of South Sumatra Province. As for the test T can be concluded that there is a significant effect of leadership (X1), motivation (X2) and intellectual ability (X3) partially to employee performance (Y) Office of the National Land Agency of South Sumatra Province.Keywords : leadership, motivation, intellectual ability, employee’s performance